Implementasi Halal Value Chain Dalam Mewujudkan Ekosistem Halal pada Produk Unggulan UD Mitra Jamur Jember - Hasanah, Miftahul; Istikomah; Muhammad Syafii (Universitas Muhammadiyah Jember, 2023)
Indonesia is a country with a majority Muslim population. As a Muslim, of course, you must obey Allah's commands and stay away from his prohibitions, such as the obligation to consume halal food. This is a form of obedience to religious law (shariah compliance). In 2024, Indonesia wants to become the center of the world's halal industry through various instruments that can make this happen. The halal industry certainly starts with instilling halal values ​​from upstream to downstream which is called the Halal Value Chain and can be internalized by all business actors so that they can realize the Islamic Ecosystem in Indonesia. This study aims to find out how the development of the halal industry in Indonesia is, how the halal value chain process on UD Mitra Mushroom's superior products creates a halal ecosystem, and how is the impact of the halal value chain on UD Mitra Mushroom's superior products to create a halal ecosystem. The research method used is descriptive qualitative with field research specifications with research subjects namely owners, members/workers, and consumers of UD products. The results of this study are that every production process at UD Mitra Mushroom is always required to comply with operational standards (SOP) that are applied continuously. The mushroom raw materials used are harvested from their own agricultural products so that their quality can be maintained. Halal certification has been obtained for several processed mushroom products obtained through halal certification assistance activities carried out by halal assistants from the Muhammadiyah University of Jember and had an impact on increasing sales turnover of these processed mushrooms